2013
DOI: 10.1002/jmr.2277
|View full text |Cite
|
Sign up to set email alerts
|

Raltegravir flexibility and its impact on recognition by the HIV‐1 IN targets

Abstract: HIV-1 IN is a pertinent target for the development of AIDS chemotherapy. The first IN-specific inhibitor approved for the treatment of HIV/AIDS, RAL, was designed to block the ST reaction. We characterized the structural and conformational features of RAL and its recognition by putative HIV-1 targets - the unbound IN, the vDNA, and the IN•vDNA complex - mimicking the IN states over the integration process. RAL binding to the targets was studied by performing an extensive sampling of the inhibitor conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 125 publications
1
11
0
Order By: Relevance
“…A slight preference for the Z-configuration of carbonylamino-hydroxypyrimidinonepharmacophore in the gas phase was observed, in coherence with the established predisposition of β-ketoenols -a principle corner stone of this pharmacophore -to adopt the Z-isomer in the solid state (Figure 9 b) [78][79][80]. The preference of aliphatic β-ketoenols to form energetically favorable Z-configurartion has been predicted early by ab initio studies at the B3LYP/3-G** level of theory [81].…”
Section: Structure and Conformational Flexibilitysupporting
confidence: 63%
See 1 more Smart Citation
“…A slight preference for the Z-configuration of carbonylamino-hydroxypyrimidinonepharmacophore in the gas phase was observed, in coherence with the established predisposition of β-ketoenols -a principle corner stone of this pharmacophore -to adopt the Z-isomer in the solid state (Figure 9 b) [78][79][80]. The preference of aliphatic β-ketoenols to form energetically favorable Z-configurartion has been predicted early by ab initio studies at the B3LYP/3-G** level of theory [81].…”
Section: Structure and Conformational Flexibilitysupporting
confidence: 63%
“…To explore the role of the HIV-1 viral DNA in RAL recognition we docked RAL onto the non-cleaved and cleaved DNA (the terminal GT nucleotides were removed) [79]. We found that RAL docked onto the non-cleaved vDNA is positioned in the minor groove of the substrate.…”
Section: Raltegravir Recognition By the Hiv-1 Targetsmentioning
confidence: 99%
“…This complex then integrates with the host’s cellular genome with the aid of lens epithelial-derived growth factor (LEDGF or p75) in the second step called strand transfer (ST), infecting the individual (Varadarajan et al 2013 ; Park et al 2021 ). Both these reactions are energetically independent as well as set apart, both spatially and temporally as the 3’P occurs in the cytoplasm of the infected cells, whereas the ST activity takes place in the nuclei (Arora et al 2013 ). Once integrated, it is now referred to as a provirus, which acts as a post-integrative template for viral infection, allowing its self-transcription to release more infectious copies of itself (Thierry et al 2017 ).…”
Section: Integrase Inhibitorsmentioning
confidence: 99%
“…This domain also encompasses a flexible 10 residues loop (140–149) that is adjacent to the catalytic site, involved in vcDNA substrate recognition. Residues 213–288: C-terminal domain (CTD) This region serves as a non-specific binding site for the vcDNA and further contributes to stabilizing the IN–vcDNA complex (Arora et al 2013 ; Ross 2015 ; Thierry et al 2017 ; Nusrath Unissa et al 2017 ; Zhou et al 2021 ). …”
Section: Integrase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation